Refining treatment planning in STereotactic Arrhythmia Radioablation: benchmark results and consensus statement from the STOPSTORM.eu consortium : physics contribution - Trojani, Valeria; Grehn, Melanie; Botti, Andrea; Balgobind, Brian; Savini, Alessandro; Boda-Heggemann, Judit; Miszczyk, Marcin; Elicin, Olgun; Krug, David; Andratschke, Nicolaus; Schmidhalter, Daniel; van Elmpt, Wouter; et al. (International journal of radiation oncology, biology, physics, 2025)
Purpose - STereotactic Arrhythmia Radioablation (STAR) showed promising results in patients with refractory ventricular tachycardia. However, clinical data are scarce and heterogeneous. The STOPSTORM.eu consortium was established to investigate and harmonize STAR in Europe. The primary goal of this benchmark study was to investigate current treatment planning practice within the STOPSTORM project as a baseline for future harmonization. - Methods and Materials - Planning target volumes (PTVs) overlapping extracardiac organs-at-risk and/or cardiac substructures were generated for 3 STAR cases. Participating centers were asked to create single-fraction treatment plans with 25 Gy dose prescriptions based on in-house clinical practice. All treatment plans were reviewed by an expert panel and quantitative crowd knowledge-based analysis was performed with independent software using descriptive statistics for International Commission on Radiation Units and Measurements report 91 relevant parameters and crowd dose-volume histograms. Thereafter, treatment planning consensus statements were established using a dual-stage voting process. - Results - Twenty centers submitted 67 treatment plans for this study. In most plans (75%) intensity modulated arc therapy with 6 MV flattening filter free beams was used. Dose prescription was mainly based on PTV D95% (49%) or D96%-100% (19%). Many participants preferred to spare close extracardiac organs-at-risk (75%) and cardiac substructures (50%) by PTV coverage reduction. PTV D0.035cm3 ranged from 25.5 to 34.6 Gy, demonstrating a large variety of dose inhomogeneity. Estimated treatment times without motion compensation or setup ranged from 2 to 80 minutes. For the consensus statements, a strong agreement was reached for beam technique planning, dose calculation, prescription methods, and trade-offs between target and extracardiac critical structures. No agreement was reached on cardiac substructure dose limitations and on desired dose inhomogeneity in the target. - Conclusions - This STOPSTORM multicenter treatment planning benchmark study not only showed strong agreement on several aspects of STAR treatment planning, but also revealed disagreement on others. To standardize and harmonize STAR in the future, consensus statements were established; however, clinical data are urgently needed for actionable guidelines for treatment planning.